Internet addiction is related to attention deficit but not hyperactivity in a sample of high school students. (March 2015) - Yılmaz, Savaş; Hergüner, Sabri; Bilgiç, Ayhan; Işık, Ümit
Abstract Objective. To assess the effects of attention-deficit/hyperactivity disorder (ADHD) symptom dimensions on Internet addiction (IA) after controlling for Internet usage features among high school students. Methods. This study consisted of 640 students (331 females and 309 males) ranging from 14 to 19 years of age. The Internet Addiction Scale, the Conners-Wells' Adolescent Self-Report Scale-Short Form, and a personal information form were completed by the participants. Statistical analyses were conducted for both sexes and the total sample. Results. According to the logistic regression analysis, attention deficit and playing online games were significant predictors of IA in both sexes. Other predictors of IA included behavioral problems for females, total weekly Internet usage time, and lifelong total Internet use for males. Hyperactivity and other Internet usage features did not predict IA. Conclusion. These results suggest that attention deficit and playing online games are important determinants of IA in this age group.